SISTEM PENGAMANAN FILE DAN CYBER SECURITY PADA PENGAMANAN OBJEK VITAL PT PDAM (Perusahaan Daerah Air Minum) - Edy Soesanto; Septiana Cahyaningrum Tarmono Putri; Annisa Azahra Aulia; Farrel Yafi Wicaksana; Rahma Fithriami Thalitha (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
File security is an act of deterrence from attacks by irresponsible file users or network accessors (Mulyana, 2016). Cyber security is security that has been modified, the nature of which refers to everything that is owned in cyberspace that is to be secured. According to (Prabuningtyas, 2018). Vital object security system is a national vital object that has a strategic role in national development. On the other hand, the dimensions of security threats and disturbances are growing with various risks and impacts. Security threats and disturbances to vital national objects directly or indirectly impact the national economic system, political stability, and national security according to (Namudat et al., 2019) PT. Regional Drinking Water Company (PDAM) Is one of the regionally owned business units, which is engaged in the distribution of clean water to the general public. There are PDAMs in every province, district, and municipality throughout Indonesia. The object of this research is the Regional Drinking Water Company (PDAM). Data collection techniques use survey techniques and research methods use a combination of descriptive and associative methods. Description of PT PDAM (Regional Water Supply Company) Regional Drinking Water Company (PDAM) is one of the BUMDs owned by the local government. Based on Law no. 5 of 1962 as a business owned by the Regional Government (Pemda) which provides services and organizes public benefits in the field of drinking water. PDAM activities start from producing, processing, and distributing clean water to customers.